Bahasa, Sastra Arab, dan Munasabah Al- Qur'an - Mukhtar Gozali (Buletin Al-Turas, 2006)
"Munasabah" is a correlation between a sentence and another sentence in a Quranic verse; between a sentence andanother sentence in Quranic verse, and between a "surah" and another "surah". "Munasabah" which a correlation between a Quranicverse and Quranic verse into 2 that is a different: One has a clear correlation and another one  that has no clear correlation.